Pulmonary Imaging of Immunocompromised Patients during Hematopoietic Stem Cell Transplantation using Non-Contrast-Enhanced Three-Dimensional Ultrashort Echo Time (3D-UTE) MRI - Metz, Corona; Böckle, David; Heidenreich, Julius Frederik; Weng, Andreas Max; Benkert, Thomas; Grigoleit, Götz Ulrich; Bley, Thorsten; Köstler, Herbert; Veldhoen, Simon (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2021)
Purpose To evaluate the feasibility of non-contrast-enhanced three-dimensional ultrashort echo time (3D-UTE) MRI for pulmonary imaging in immunocompromised patients during hematopoietic stem cell transplantation (HSCT).Methods MRI was performed using a stack-of-spirals 3D-UTE sequence (slice thickness: 2.34mm; matrix: 256 × 256; acquisition time: 12.7–17.6 seconds) enabling imaging of the entire thorax within single breath-holds. Patients underwent MRI before HSCT initiation, in the case of periprocedural pneumonia, before discharge, and in the case of re-hospitalization. Two readers separately assessed the images regarding presence of pleural effusions, ground glass opacities (GGO), and consolidations on a per lung basis. A T2-weighted (T2w) multi-shot Turbo Spin Echo sequence (BLADE) was acquired in coronal orientation during breath-hold (slice thickness: 6.00mm; matrix: 320 × 320; acquisition time: 3.1–5.5 min) and read on a per lesion basis. Low-dose CT scans in inspiration were used as reference and were read on a per lung basis. Only scans performed within a maximum of three days were included in the inter-method analyses. Interrater agreement, sensitivity, specificity, positive and negative predictive values, and diagnostic accuracy of 3D-UTE MRI were calculated.Results 67 MRI scans of 28 patients were acquired. A reference CT examination was available for 33 scans of 23 patients. 3D-UTE MRI showed high sensitivity and specificity regarding pleural effusions (n = 6; sensitivity, 92 %; specificity, 100 %) and consolidations (n = 22; sensitivity 98 %, specificity, 86 %). Diagnostic performance was lower for GGO (n = 9; sensitivity, 63 %; specificity, 84 %). Accuracy rates were high (pleural effusions, 98 %; GGO, 79 %; consolidations 94 %). Interrater agreement was substantial for consolidations and pleural effusions (κ = 0.69–0.82) and moderate for GGO (κ = 0.54). Compared to T2w imaging, 3D-UTE MRI depicted the assessed pathologies with at least equivalent quality and was rated superior regarding consolidations and GGO in ~50 %.Conclusion Non-contrast 3D-UTE MRI enables radiation-free assessment of typical pulmonary complications during HSCT procedure within a single breath-hold. Yet, CT was found to be superior regarding the identification of pure GGO changes.Key Points: Citation Format
Keywords: thorax; infection; ultrashort echo time; magnetic resonance imaging; pulmonary imaging; hematopoietic stem cell transplantation